Characteristic morphological changes in anti-VEGF therapy induced glomerular microangiopathy - Pfister, Frederick; Amann, Kerstin Ute; Daniel, Christoph; Klewer, Monika; Büttner, Anke; Büttner-Herold, Maike (Histopathology, 2018)
BACKGROUND: Thrombotic microangiopathy (TMA) is a microvascular pathology caused by several drugs used in cancer therapy. Agents targeting vascular endothelial growth factor (VEGF) have increasingly been used in therapy of advanced malignancies and have been found to induce renal TMA and proteinuria. However, histomorphological changes in human biopsies in this setting and the underlying mechanism are not yet fully understood. METHODS: Renal biopsies of 15 patients with anti-VEGF therapy (aVEGF) evaluated between 2013 and 2017 at a single centre were morphologically characterized using light microscopy, electron microscopy and immunohistochemistry (IgA, IgG, IgM, C1q, C3) and compared to cases with acute TMA caused by atypical haemolytic uramic syndrome or hypertension. Morphological overlap with immune-complex and cryoglobulinemic membranoproliferative glomerulonephritis, diabetic glomerulopathy and pre-emclapsia induced glomerulopathy were discussed. RESULTS: Segmental glomerular capillary microaneurysms and segmental hyalinosis were typical morphological features of aVEGF therapy induced glomerular microangiopathy, whereas fibrin or platelet thrombi or fragmented erythrocytes were rarely found or absent. aVEGF therapy associated microangiopathy was diffusely distributed in the glomeruli, spared pre-glomerular vessels, and showed morphological characteristics of chronic TMA. In individual cases, aVEGF therapy induced glomerular microangiopathy was accompanied by immune-complex glomerulonephritis. CONCLUSION: aVEGF therapy induced glomerular microangiopathy has a characteristic morphology and clinical presentation that helps to differentiate it from other causes of TMA. Awareness of these light microscopic findings allows identification of aVEGF therapy as a trigger of renal disease in critically ill cancer patients and therefore might help in deciding on further therapy. This article is protected by copyright. All rights reserved.
EVALuna2:34420